2020
DOI: 10.3390/ijms21217811
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Arginine with Gestational Diabetes Mellitus in a Follow-Up Study

Abstract: In the reported study we applied the targeted metabolomic profiling employing high pressure liquid chromatography coupled with triple quadrupole tandem mass spectrometry (HPLC–MS/MS) to understand the pathophysiology of gestational diabetes mellitus (GDM), early identification of women who are at risk of developing GDM, and the differences in recovery postpartum between these women and normoglycemic women. We profiled the peripheral blood from patients during the second trimester of pregnancy and three months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…They play a role in cellular systems and are associated with vascular disease and cancer. Their concentrations, determined by high-performance liquid chromatography (HPLC) and HPLC-MS/MS, differ in pregnant women with GDM compared to healthy pregnant women; cysteine concentrations are higher in GDM, whereas methionine concentrations are lower, and the results for homocysteine concentrations are conflicting ( 18 , 40 , 41 ).…”
Section: Amino Acid and Fatty Acids Profilingmentioning
confidence: 99%
“…They play a role in cellular systems and are associated with vascular disease and cancer. Their concentrations, determined by high-performance liquid chromatography (HPLC) and HPLC-MS/MS, differ in pregnant women with GDM compared to healthy pregnant women; cysteine concentrations are higher in GDM, whereas methionine concentrations are lower, and the results for homocysteine concentrations are conflicting ( 18 , 40 , 41 ).…”
Section: Amino Acid and Fatty Acids Profilingmentioning
confidence: 99%
“…Despite the fact that the associations of several amino acids, such as branched-chain amino acids [ 60 ], methionine [ 61 ], and phenylalanine [ 45 ], with GDM risk have been widely described, the crucial role of arginine in the pathogenesis of GDM and its potential to be a good predictor in the earlier detection of this disease has attracted increasing attention. A recent systematic screening conducted in the GDM pregnancies with targeted metabonomics found that an arginine-based model showed the best prediction performance for diabetic status [ 13 ], which was further confirmed by a consensus multivariate analysis showing that urine arginine concentration in the first trimester has the highest accuracy in predicting GDM cases [ 62 ]. These findings have shed light on the critical role of arginine in the development of GDM.…”
Section: Discussionmentioning
confidence: 95%
“…The association between the maternal arginine concentration and GDM was reported in 14 case–control studies [ 13 , 19 , 20 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], comprising 416 patients and 736 normal pregnancies. A meta-analysis indicated that the appearance of GDM was accompanied by a higher maternal arginine concentration (SMD: 0.46; 95% CI: 0.11, 0.81; I 2 = 82.3%, Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burzynska-Pedziwiatr et al [ 20 ] performed the targeted metabolomic profiling in patients with GDM during gestation and postpartum period and revealed that the downregulation of arginine played a critical role in the development of GDM and in addition may also predict increased risk of type 2 diabetes mellitus.…”
mentioning
confidence: 99%